A Review on Prescription Opioid Abuse - Are Abuse Deterrent Formulations a Solution - Vijay Sehgal,; Singla R, (GMC Patiala Journal of Research and Medical Education, 2018)
Non-medical prescription opioid drug use is a growing problem in India. The development of abuse-deterrent formulations (ADFs) of prescription opioid analgesics is a novel strategy toward reducing abuse and diversion of these medications. However, drug abuse still remains a problem as the addict may switch over to other accessible non abuse-deterrent opioids. Moreover opioid ADFs may themselves be abused via the intended route of administration by increasing the dose or dosing frequency. This review stresses upon the need to further elucidate the risk and benefit of long term opioid therapy and ADFs in the management of chronic non-malignant pain.